Análise de processos de erosão celerada, com base em fotografias aéreas e geoprocessamento: Bacia do Rio Bonito (Descalvado, SP) - Feres, Roberto (2002)
This study relates the methodology adopted to organize the information on the abiotic environment related to the characterization of erosive processes visible in aerial photographs in order to contribute towards actions of planning of the drainage basin of the Bonito river, a sub-basin of the Mogi-Guaçu river, in the municipality of Descalvado-SP, Brazil. The area of study is part of a region highly susceptible to erosive phenomena as a result of favorable conditions provided by the unconsolidated cover material, easily erodible. The environmental fragility of the terrains, however, contrasts with the great fragmentation of the landscape. Under a GIS single georeferenced database at a 1:50,000-compatible scale, all available cartographic and sampling information was organized and compared with a photo mosaic adjusted to a cartographic base of the same area at a 1:10,000 scale, and a visual analysis of the features was performed by photo interpreting. A preliminary map of the unconsolidated material was developed from the information regarding the geological surface formations correlated with the field slope patterns, allowing the automation of the mapping in GIS. The field inspection, aided by real time navigation system on the cartographic information, made possible to diagnose the events found there. The organization applied to the collected information allows the planner to understand each individual developed feature, their causes and the reasons that contribute to it s persistence, correlating them with the local patterns of the environment fragility and compounding an overview of the events that occur in hydrographic basin as a whole.